AQUA AMMONIA ELECTROLYTIC CHARACTER AND TPP COOLANT CONDUCTOMETRIC QUALITY CONTROL UNDER HIGH TEMPERATURES AND PRESSURES - Vladimir Nikolayevich Shcherbakov; Grigory Andreyevich Vlaskov (Advanced Engineering Research, 2013)
To improve the operational conductometric steam quality control at the TPP, CHPP, and NPP, the technique for NaCl and NH4OH concentration in the saturated and superheated steam of the high- and supercritical pressure steam generators is developed, and a device for its implementation is offered. The error of determination in the range of the concentrations specific for the operated power plants is estimated. The equations describing the behavior of the thermodynamic dissociation constant, and limiting equivalent conductance of NH4OH in a wide range of state parameters that can be used in calculating the concentrations according to the proposed technique, as well as in water chemistry organization and management, are proposed. The assessment of the approximation error of dependences for the experimental data on the dissociation constants and limiting equivalent conductance is given.